Nine new species of the Anaulacomerina subtribe of katydids (Orthoptera: Tettigoniidae: Phaneropterinae: Phaneropterini) from Brazil - Fianco, Marcos (Zootaxa, 2021)
Nine new species of katydids of the Anaulacomerina subtribe (Orthoptera: Tettigoniidae: Phaneropterinae: Phaneropterini) are herein described, being eight of the genus Anaulacomera Stål and one of Separatula Gorochov. The following species are described as new: A. (Anallomes) sylviae sp. n., A. (Anaulacomera.) caudata sp. n., A. (Anaul.) rubrovittata sp. n., A. (Anaul.) zefai sp. n., A. (Oecella) marshae sp. n., A. (O.) mediastina sp. n., A. (O.) spirala sp. n., A. (O.) zebrina sp. n. and S. araguaiensis sp. n. External morphological characters as tegmina venation, cerci and subgenital plate; and internal morphological characters as male genitalia are included in the descriptions.